Biomonitoring of Heavy Metal Toxicity in Freshwater Canals in Egypt Using Creeping Water Bugs (Ilyocoris cimicoides): Oxidative Stress, Histopathological, and Ultrastructural Investigations - Lamia M. El-Samad; Esraa A. Arafat; Ola Mohamed Nour; Nessrin Kheirallah; Mohammed E. Gad; Mohamed Hagar; Zeinab A. El-Moaty; Mohamed A. Hassan (Antioxidants, 2024)
The abundance of metal pollutants in freshwater habitats poses serious threats to the survival and biodiversity of aquatic organisms and human beings. This study intends for the first time to assess the pernicious influences of heavy metals in Al Marioteya canal freshwater in Egypt, compared to Al Mansoureya canal as a reference site utilizing the creeping water bug (Ilyocoris cimicoides) as an ecotoxicological model. The elemental analysis of the water showed a significantly higher incidence of heavy metals, including cadmium (Cd), cobalt (Co), chromium (Cr), nickel (Ni), and lead (Pb), in addition to the calcium (Ca) element than the World Health Organization’s (WHO) permitted levels. The Ca element was measured in the water samples to determine whether exposure to heavy metals-induced oxidative stress engendered Ca deregulation in the midgut tissues of the creeping water bug. Remarkably, increased levels of these heavy metals were linked to an increase in chemical oxygen demand (COD) at the polluted site. Notably, the accumulation of these heavy metals in the midgut tissues resulted in a substantial reduction in antioxidant parameters, including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and ascorbate peroxidase (APOX), along with a marked rise in malondialdehyde (MDA), cytochrome P450, and protein carbonyl levels. These results clearly indicate a noticeable disturbance in the antioxidant defense system due to uncontrollable reactive oxygen species (ROS). Notably, the results demonstrated that oxidative stress caused disturbances in Ca levels in the midgut tissue of I. cimicoides from polluted sites. Furthermore, the comet and flow cytometry analyses showed considerable proliferations of comet cells and apoptotic cells in midgut tissues, respectively, exhibiting prominent correlations, with pathophysiological deregulation. Interestingly, histopathological and ultrastructural examinations exposed noticeable anomalies in the midgut, Malpighian tubules, and ovarioles of I. cimicoides, emphasizing our findings. Overall, our findings emphasize the potential use of I. cimicoides as a bioindicator of heavy metal pollution in freshwater to improve sustainable water management in Egypt.